Kouření a rakovina prsu - Hrubá, D (Klinicka onkologie, 2013)
BACKGROUND: Investigation of the relationship between smoking and breast cancer risk did not show a consensus in results - some studies described smoking as a risk factor, while others found its effects protective. PURPOSE: The newest studies explain these differences by the genetic polymorphism. Cigarette smoke contains at least 20 chemical carcinogens, which are deposited and metabolically activated in the breast and surrounding adipose tissues. The substances are further detected in the nipple discharge or as smoking specific DNA adducts in breast tissue. Several studies postulate significantly higher risk of breast cancer among women who started smoking at an early age and/ or before their first delivery. Some studies from Japan, China, California have shown that longterm exposure to passive smoking could significantly increase the risk of breast cancer in never smokers, while other scientist reject the evidence of this association as inconsistent. A possible protective effect of smoking on the incidence of breast cancer is explained by antiestrogenic activity of smoking, namely nicotine. CONCLUSION: Smoking may play a role in the breast cancer incidence. Due to a wide spectrum of harmful effects of smoking, and with regards to the worse prognosis of breast cancer among smoking patients, the common recommendations for cancer prevention are similarly plausible in case of breast cancer - no smoking, no alcohol, fruit and vegetable consumption, physical activity and body weight control.
Keywords: rizikové faktory; Smoking; znečištění tabákovým kouřem; hodnocení rizik; Incidence; Tobacco Smoke Pollution; lidé; Female; nádory prsu; ženské pohlaví; Risk Assessment; incidence; Breast Neoplasms; Humans; kouření; Risk Factors